A combined approach for sustainable use of mountainous agricultural land: land suitability evaluation and ecological economic model - Hoang, Thi Huyen Ngoc; Nguyen, Manh Ha; Bui, Quang Dung (Vietnam Journal of Earth Sciences, 2022)
In the quest for poverty reduction, developing sustainable agriculture and stabilizing cultivation areas for specialty plants can be substantially improved by a new approach, which combines land suitability assessment and designs of ecological-economic models. The land suitability was assessed according to the FAO framework and the Vietnamese standard TCVN-8409:2012. The criteria were grouped in the parameters of climate, topography, and soil physicochemical properties. The seven land utilization types selected for analysis included orange, banana, tea, turmeric, cinnamon, chinaberry, and chukrasia in mountainous regions of Thanh Hoa and Nghe An Provinces, Vietnam. The results showed that the most suitable lands (S1) for cultivating these crops were 169.916 ha for orange, 201.166 ha for banana, 107.636 ha for tea, and 570.744 ha for turmeric, 233.987 ha for cinnamon, 633.306 ha for chinaberry, and 280.704 ha for chukrasia. Based on that foundation, the study designed three ecological models with economic efficiency and elaborated on six formations of the models. The analyses obtained from the research also allowed the proposal of six prioritized spaces for land use and environmental protection, which were illustrated on a 1:100,000 map of proposed agricultural land use. Therefore, this study provided a detailed and reliable approach for researchers and managers in agricultural land use planning. A proper procedure for the assessment of agricultural land in mountainous areas can be suggested from this research.